Future time reference in Lule Saami, with some remarks on Finnish - Ylikoski, Jussi (Eesti ja soome-ugri keeleteaduse ajakiri. Journal of Estonian and Finno-Ugric Linguistics, 2016)
The paper provides an account of future time reference (FTR) in Lule Saami. While previous accounts of the language claim that the Lule Saami galggat ‘shall; must; intend’ is a future auxiliary, there are two other potential candidates for what might be called a future tense as well. On the basis of actual language use, the potential mood in Lule Saami does not always refer to states of affairs to be understood as uncertain or only possible, but is also used to refer to future events with no visible shades of possibility or other modalities. Special attention is given to another grammaticalized construction, a periphrastic form consisting of the copula liehket ‘be’ and a purposive converb (supine). Further, it is shown that the Lule Saami supine construction has a formal and functional analogue in the previously undescribed, future-like aspectual functions of the purposive converb in Finnish.